2008
DOI: 10.1177/0193945907303107
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Rurality, Home Health Care Use, and Outcomes

Abstract: Rural elders have a disproportionate prevalence of illness and limited access to health services. The purpose of this study is to determine whether degree of rurality and home health care use influences home health care patient outcomes. An adaptation of the Outcomes Model for Health Care Research provided the framework for the study. A stratified random sample was selected from a database of risk-adjusted publicly reported patient outcomes from Medicare-certified home health care agencies and merged with agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…The questionnaire on the characteristics of the home care organisations was developed on evidence-based literature on community care organisations and quality of care [59606162636465]. Elements concerning integrated care were included based on the theoretical framework of the Care Coordination Atlas [65].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire on the characteristics of the home care organisations was developed on evidence-based literature on community care organisations and quality of care [59606162636465]. Elements concerning integrated care were included based on the theoretical framework of the Care Coordination Atlas [65].…”
Section: Methodsmentioning
confidence: 99%
“…Between 2002 and 2010, an increasing proportion of both urban and rural beneficiaries used HH services; in 2011 and 2012, these proportions declined, coincident with drops in payment per episode (MEDPAC, 2014b, Table 6). Rural HH agencies are particularly susceptible to payment changes given the higher operating costs, limited availability of providers, and long travel distances (Sutton, 2005a;Vanderboom & Madigan, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that rural beneficiaries used more Medicare HH services (McAuley, Spector, Van Nostrand, & Shaffer, 2004), received more HH visits per episode (Kenney, 1993b), and had more direct care time (Adams et al, 2001) compared to their urban peers. Other studies suggested that rural beneficiaries received fewer HH services compared to urban beneficiaries (Kenney, 1993a;Mitchell, Strain, & Blandford, 2007;Murtaugh, McCall, Moore, & Meadow, 2003;Schlenker et al, 2002;Vanderboom & Madigan, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McAuley, Spector, and Van Nostrand (2009) found that adults living in remote areas received fewer days of home care, suggesting a possible access problem. Vanderboom and Madigan (2008) reported that rural home care and home support agencies provided fewer visits per patient, which they speculate may be linked to the availability of human and financial resources. Forbes and Janzen (2004) found that rural home care and home support users are more likely than their urban counterparts to receive help with housework and less likely to receive help with personal care.…”
Section: Introductionmentioning
confidence: 99%